The effect of type 2 diabetes mellitus on clinical symptoms, sputum molecular test results, and lesions in thoracic photos of pulmonary tuberculosis patients - Fikriatul Fadhilah; Erwin Arief; Nur Ahmad Tabri; Irawaty Djaharuddin; Arif Santoso; Jamaluddin Madolangan (Italian Journal of Medicine, 2025)
Pulmonary tuberculosis (TB) remains a major global health issue, particularly in developing countries. Type 2 diabetes mellitus (T2DM) has been linked to increased susceptibility and more severe TB presentations, though evidence on its impact remains inconsistent. This prospective cohort study, conducted at RSUP Dr. Wahidin Sudirohusodo Makassar from August to November 2024, evaluated 90 bacteriologically confirmed pulmonary TB patients, with and without T2DM. Clinical symptoms, sputum molecular test (RMT) results, and radiographic lesion extent were assessed. TB patients with T2DM showed significantly more severe symptoms (p=0.002), more extensive lung lesions (p=0.008), and a lower rate of RMT positivity (p=0.033). These findings suggest that T2DM is associated with more severe disease manifestations and broader lung involvement but reduced molecular test positivity in pulmonary TB patients.